Three-dimensional pattern recognition with a single two-dimensional synthetic reference function - Li, Y; Rosen, J (Applied optics (2004), 2000)
A novel, to our knowledge, method of distortion-invariant three-dimensional (3-D) pattern recognition is proposed. A single two-dimensional synthetic discriminant function is employed as a reference function in the 3-D correlator. Thus the proposed system is able to identify and locate any true-class object in the 3-D scene. Preliminary simulation and experimental results are presented.